Compétences spatiales, compétences d’action dans l’espace - Céline Cholez (Revue d'anthropologie des connaissances)
In this article, we show that the way a delivery round is organized and executed is more complicated than the designers of the delivery real-time software could presume (in regard with the criterion they use to conceive their software). Like others professionals nomads (postman, usher), the deliverymen spatial skills’ are a material knowledge and a social knowledge. We use the situated action and the social cognition approach to show that the deliverymen’s task needs a work of articulation between different worlds. This work of articulation is optimized with a calculation made when the deliverymen prepare their rounds and during the rounds. They use different spatial devices. These devices give some different viewpoints of the space to travel in.